A rare case of Thoracic Aortic Aneurysm repair post Heart Transplantation - Helena Garcia Betinardi Bernardi; Cristhian Espinoza Romero; Vanessa Simioni Faria; Fabiana G. Marcondes-Braga; Fabio A. Gaiotto; Fernando Bacal (JHLT Open)
During bicaval orthotopic heart transplant (HT), two segments of the aorta are generated, separated by a suture line. Both segments are exposed to the same systemic environment. Nevertheless, it has been observed that aneurysmal disease is confined to one of the segments of aorta. We report here a successful repair of AA, confined to the donor portion of aorta, in a HT recipient after 12 years of transplant.